To Assess Knowledge of Basic Life Support among Dental Graduates in Terms of Handling Medical Emergencies - Rafay Manan, Shahid Ali, Adnan Haider, Muhammad Ali, Ali Farooq, Kashif Khattak (Pakistan Journal of Medical & Health Sciences, 2023)
Aims and objective: Dentists being part of health care providers often encounter with medical emergencies in their dental office, some are trained to cope with, but a large number of dentists lack knowledge and proper training to handle such emergencies results in serious consequences and medicolegal actions. This study will reflect and encourage knowledge and confidence of dental graduates to deal with such situations. Study design: It was a cross sectional study to asses knowledge and management skills of dental graduates, gained during their study in dental college. Place and duration of study: Study comprised of three months’ time (March 2022 to May 2022) in which data was collected from de’Montmorency college of dentistry and Fatima memorial dental college, Lahore. Materials and methods: A self-designed questionnaire was distributed among 98 dental graduates in Lahore. Questionnaire comprised of eleven questions inquiring about medical emergency encountered in their dental clinic/hospital, Basic Life support(BLS), cardiopulmonary resuscitation(CPR), emergency drugs, and equipment and their proper administration and if they want to attend a BLS course in future. Analyzing of data done by statistical package for social sciences SPSS 20.0. Conclusion: Majority of participants were short of confidence regarding executing the chain of BLS. Some participants were having not enough knowledge of location of chest compressions during CPR. Though a good fraction of participants were aware of emergency drugs and equipment but were not enough confident to use them. Majority were agreeing to attend a proper BLS course to strengthen their knowledge and skills to deal medical emergencies. Keywords: Basic Life Support, Cardiopulmonary Resuscitation, Emergency Drugs, Dental Graduates